2022
DOI: 10.7759/cureus.28144
|View full text |Cite
|
Sign up to set email alerts
|

Ill Effects and Complications Associated to Removable Dentures With Improper Use and Poor Oral Hygiene: A Systematic Review

Abstract: The importance of oral care and its relationship with an individual's well-being has been identified over the past few decades. As there is a drastic increase in the aging population, so did the use of removable dentures more than ever before. The use of dentures among the elderly provides functional advantages and esthetic benefits. However, improper use and poor oral hygiene with removable dentures come with complications, including denture stomatitis, ulcerations, pneumonia, and many more. The study aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Recently, De Souza et al [ 28 ] reported that individuals with low socioeconomic status are more likely to develop DS due to poor access to routine medical care. An association relationship between DS and other diseases, such as pneumonia and bacterial endocarditis, is also reported [ 3 , 19 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, De Souza et al [ 28 ] reported that individuals with low socioeconomic status are more likely to develop DS due to poor access to routine medical care. An association relationship between DS and other diseases, such as pneumonia and bacterial endocarditis, is also reported [ 3 , 19 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dentures provide a microenvironment that encourages Candida colonization [ 14 ]. The longstanding use of dentures in patients with poor oral hygiene allows the dental biofilm (plaque) to colonize the surface of the prosthesis and the mucosal surfaces in contact with the denture base [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Однако при реабилитации пациентов пожилого возраста с частичной и полной адентией при помощи съемных зубных протезов возникают определенные сложности. Неправильное использование и плохая гигиена полости рта при использовании съемных зубных протезов приводят к осложнениям, включая стоматит, язвы, пневмонию и многое другое [ 4 ] .…”
unclassified